THE CONCEPTUAL STUDY OF STHAULYATA W.S.R. TO OBESITY - Sunil P, Nikhate; Dattatrey T, Kodape (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda is one of the most ancient medical sciences of the world. It conceives and describes the basic and applied aspects of life process, health, disease and its management in terms of its own principles and approaches. In Ayurveda, Sthaulya has been described since very early days in various Samhitas, Sangraha Granthas etc. Acharya Charaka has described Sthaulya among the eight most unwanted diseases (Nindita Purusha) and Samtarpanajanita Roga. The term Medasvi is suggestive of nutritional status of the individuals indicating a well nourished disposition rather than disease. Sthaulya is involving the Medovriddhi which deals with study of typical obesity that is a reflection of endocrine imbalance, not with the reasonal adiposity. Obesity is the most common nutritional (metabolic) disorder in wealthy societies. Sthaulya (obesity) is discouraged by the society for social as well as medical reason. Commonly obesity is due to excessive eating and lack of adequate exercise. Three main causes have been described in modern literature viz. 1) Dietetic, 2) Genetic, 3) Hormonal. Dalhana seems to be more explicit while commenting on a Medo Roga specified that Agni which is involved in pathogenesis of the disease viz. Dhatvagnimandya. In pathogenesis of Sthaulya, Kledaka Kapha, Samana & Vyana Vayu, Meda (fat /lipid) and Medodhatvagni Mandyata are main responsible factors. So that type of therapy should be selected, this can effect on all these factors. We all are accepting the concept prevention is better than cure. So after looking the vital importance of obesity (Sthaulya), it is selected for the present conceptual study.